(untitled) (Teología, 2016)
This report is part of the first Opening Panel of the 2nd Congress of Latin-American and German theologians, named “Spaces of Peace”, carried out from the 28th through the 31st of March, 2016. It presents the theme of peace as a sign of the present time, from three standpoints: the Latin-American context, the centrality of violence in the studies on peace and its relation to women as peacemakers and victims of violence. The reflection is organized in two parts: firstly, the theological pastoral discernment of peace made by the conference of Medellin is analyzed in a context of underdevelopment and injustice characterized as institutional violence and structural sin. It also briefly mentions the challenges for reconciliation that were posed by the transition processes that followed the military governments and the internal armed conflicts. Secondly, some of the values and areas of peace and violence are focused on (in the personal, structural and cultural levels) in order to consider the secular and Christian concept of peace building and the theoretical and practical contribution of women in the construction of peace in a violent context.